(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the current status of quality of life (QOL) and identify the impacts of residential environments and language adaptation barriers, aiming to optimize support efficacy for Indian medical students at Dai Nam University. Materials and Methods: A mixed-methods cross-sectional study was conducted on N = 195 Indian students during the second semester of the 2025–2026 academic year. Quantitative data utilized the WHOQOL-BREF tool (transformed to a 100-point scale) and multiple linear regression models. Qualitative data from semi-structured in-depth interviews provided empirical triangulation. Results: QOL scores were highest in the social relationships domain (65.30), followed by physical health (62.45), psychological health (58.12), and living environment (56.85). Notably, 69.74% of students frequently experienced emotional stress during the initial transition. Regression analysis indicated that dormitory space conditions were simultaneously associated with sleep quality (β = 0.296) and daily energy levels (β = 0.3008, p < 0.001). Qualitative insights highlighted demands for optimizing room sharing density, thoroughly managing seasonal room mold/humidity, overcoming "tonal anxiety" in local communication, and adapting to academic English accents. A major highlight was the peer support network within the dormitories, which functioned effectively as an emotional support system, greatly facilitating student integration. Conclusions: Upgrading residential spaces and strengthening linguistic support are pivotal solutions to elevate international students’ QOL. The university is recommended to continue adjusting dormitory density, upgrading facility infrastructure, and developing applied clinical Vietnamese training programs.